Ethnic and religious factors in political and cultural development of modern Ukraine and the problem of chaplaincy - Nepipenko, L. P. (Honor and Law, 2019)
The article focuses on the problematical character of chaplaincy introduction, as political and institutional side of religious revival and strengthening of religious identifications in the political and cultural realities of modern Ukraine.